Antiviral state against influenza virus neutralized by microinjection of antibodies to interferon-induced Mx proteins. - Arnheiter, H (1988)
In mouse Mx+ cells, interferon alpha/beta induces the synthesis of the nuclear Mx protein, whose accumulation is correlated with specific inhibition of influenza viral protein synthesis. When Mx+ mouse cells are microinjected with the monoclonal anti-Mx antibody 2C12, interferon alpha/beta still induces Mx protein, but no longer inhibits efficiently the expression of influenza viral proteins as visualized by immunofluorescent labeling. However, interferon inhibition of an unrelated control virus, vesicular stomatitis virus, remains unchanged. Proteins with homology to mouse Mx protein are found in interferon-treated cells of a variety of mammalian species. In rat cells, for instance, rat interferon alpha/beta induces three Mx proteins which all cross-react with antibody 2C12 but differ in mol. wt and intracellular location, and it protects these cells well against influenza viruses. However, when rat cells are microinjected with antibody 2C12, interferon alpha/beta cannot induce an efficient antiviral state against influenza virus infection, whereas protection against vesicular stomatitis virus is not altered. These results show that both mouse and rat cells require functional Mx proteins for efficient protection against influenza virus. They further demonstrate that microinjection of antibodies is a promising way of elucidating the role of particular interferon-induced proteins in the intact cell.